Carotid CTA: Radiation Exposure and Image Quality with the Use of Attenuation-Based, Automated Kilovolt Selection - Eller, A.; Wüst, Wolfgang; Kramer, Manuel; May, Matthias; Schmid, A.; Uder, Michael; Lell, Michael (American Journal of Neuroradiology, 2014)
CTA is considered the imaging modality of choice in evaluating the supraaortic vessels in many institutions, but radiation exposure remains a matter of concern. The objective of the study was to evaluate a fully automated, attenuation-based kilovolt selection algorithm in carotid CTA in respect to radiation dose and image quality compared with a standard 120-kV protocol.Ninety-eight patients were included: 53 examinations (patient age, 66 ± 12 years) were performed by use of automated adaption of tube potential (80-140 kV) on the basis of the attenuation profile of the scout scan (study group), and 45 examinations (patient age, 67 ± 11 years) were performed by use of a standard 120-kV protocol (control group). CT dose index volume and dose-length product were recorded from the examination protocol. Image quality was assessed by ROI measurements and calculations of SNR and contrast-to-noise ratio. Subjective image quality was evaluated by 2 observers with the use of a 4-point scale (3, excellent; 0, not diagnostic).Subjective image quality was rated as "excellent" or "good" in all examinations (study group, 2.8; control group, 2.8). The algorithm automatically selected 100 kV in 47% and 80 kV in 34%; 120 kV was retained in 19%. An elevation to 140 kV did not occur. Compared with the control group, overall CT dose index volume reduction was 33.7%; overall dose-length product reduction was 31.5%. In the low-kilovolt scans, image noise and mean attenuation of ROIs inside the carotid arteries were significantly higher than in 120-kV scans, resulting in a constant or increased (80-kV group) contrast-to-noise ratio.The attenuation-based, kilovolt selection algorithm enables a dose reduction of >30% in carotid artery CTA while maintaining contrast-to-noise ratio and subjective image quality at adequate levels.
EVALuna2:14326